Obstructive sleep apnea, nighttime arousals, and leukocyte telomere length: the Multi-Ethnic Study of Atherosclerosis. Issue 7 (17th April 2019) - Carroll, Judith E; Irwin, Michael R; Seeman, Teresa E; Diez-Roux, Ana V; Prather, Aric A; Olmstead, Richard; Epel, Elissa; Lin, Jue; Redline, Susan
Abstract: Study Objectives: Sleep disturbances and sleep apnea are associated with increased vulnerability to age-related disease, altering molecular pathways affecting biological aging. Telomere length captures one component of biological aging. We evaluated whether objectively assessed sleep and sleep apnea relate to leukocyte telomere length (LTL) in the Multi-Ethnic Study of Atherosclerosis (MESA). Methods: Men and women aged 44–84 years ( n = 672) from the MESA Stress and MESA Sleep studies underwent polysomnography and 7 day actigraphy (at Exam 5) and assessment of LTL (at baseline [Exam 1] and about 10 years later [Exam 5]). Results: General linear models adjusting for age, sex, race/ethnicity, BMI, physical activity, and smoking found that severe obstructive sleep apnea (OSA; apnea–hypopnea index > 30) was cross-sectionally associated with shorter LTL ( p = 0.007). Modest associations of shorter LTL with less rapid eye movement sleep, more stage 1 sleep, wake after sleep onset >30 min, and long sleep duration were found, but these effects were diminished after adjusting for lifestyle and OSA. Exploratory analyses found that higher arousal index at Exam 5 was associated with greater LTL decline over the prior 10 years ( p = 0.004). Conclusions: OSA was associated with shorter LTL. Individuals with high-arousal frequency had greater leukocyte telomere attrition over the prior decade. These findings suggest that sleep apnea and sleep fragmentation are associated with accelerated biological aging.